The suspension of the validity of a legal act in the constitutional justice model of Lithuania - Pūraitė-Andrikienė, Dovilė (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Paragraph five of Article 106 of the Constitution of the Republic of Lithuania provides that, the presentation by the President of the Republic for the Constitutional Court or the resolution of the Seimas asking for an investigation into the conformity of an act with the Constitution shall suspend the validity of the act. The suspension of validity of legal act is regulated in more detail in Article 26 of the Law on the Constitutional Court. However, in recent years the practice of application of this institute and the concept of this institute formed in the jurisprudence of the Constitutional Court are receiving a very wide discussion in the Lithuanian legal community and in the public in general. This article seeks to reveal the problematic aspects of the provisions of the Constitution and the Law on the Constitutional Court regulating the institute of suspension of the validity of legal act, as well as the problematic aspects of the conception of this institute formed in the jurisprudence of the Constitutional Court and to make proposals on how to improve the legal framework governing this institute.